Insulin Signaling Regulates Mitochondrial Function in Pancreatic β-Cells - Liu, Siming (Public Library of Science, 2009)
Insulin/IGF-I signaling regulates the metabolism of most mammalian tissues including pancreatic islets. To dissect the mechanisms linking insulin signaling with mitochondrial function, we first identified a mitochondria-tethering complex in β-cells that included glucokinase (GK), and the pro-apoptotic protein, BAD(S). Mitochondria isolated from β-cells derived from β-cell specific insulin receptor knockout (βIRKO) mice exhibited reduced BAD(S), GK and protein kinase A in the complex, and attenuated function. Similar alterations were evident in islets from patients with type 2 diabetes. Decreased mitochondrial GK activity in βIRKOs could be explained, in part, by reduced expression and altered phosphorylation of BAD(S). The elevated phosphorylation of p70S6K and JNK1 was likely due to compensatory increase in IGF-1 receptor expression. Re-expression of insulin receptors in βIRKO cells partially restored the stoichiometry of the complex and mitochondrial function. These data indicate that insulin signaling regulates mitochondrial function and have implications for β-cell dysfunction in type 2 diabetes.